Dissimilar welding of A7075-T651 and AZ31B alloys by gas metal arc plug welding method. Issue 9 (February 2017) - Islam, M.; Ishak, M.; Shah, L.; Idris, S.; Meriç, C.
Abstract Innovative welding techniques allow for the fabrication of light, high-specific-strength, and fuel-saving Al and Mg alloys for use in transportation industries. Furthermore, these techniques have minimal detrimental impact on the environment. However, the poor mechanical properties of joints resulting from the formation of brittle Alm Mgn intermetallic compounds are key barriers to joining Al and Mg alloys. To date, a proper solution to this problem has not yet been provided. The aim of this research was to investigate the mechanical and metallurgical properties of the joint between AZ31B and A7075-T651 alloys welded by a new technique called gas metal arc plug welding method. ER5356 aluminum wire was used as a filler. The yield and ultimate tensile strengths as well as impact toughness of the joints were measured. The fracture surface was investigated by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The maximum ultimate tensile strength and impact toughness of the joints were 89 and 84 % of those of the AZ31B parent alloy, respectively. Generally, the joints failed in the ER5356 nugget, whereas some failed in the AZ31B alloy. No fracture was observed in the A7075-T65 alloy. Brittle fracture mechanism was observed for all the joints. In conclusion, the proposed welding technique can allow for better mechanical properties of joints for dissimilar welding of aluminum and magnesium alloys.